HEGEMONI DALAM NOVEL TRILOGI KARYA AHMAD TOHARI: KAJIAN SOSIOLOGI SASTRA - Adiyatno, Sam Devi; Lembah, Gazali; Kangiden, Nurhaya (BAHASANTODEA, 2016)
The objective of this research was to describe of hegenomy in the novel trilogi by Ahmad Tohari. The theory was used that theory of hegenomy based on the an opinion by Marxis and Gramsci. This research was a qualitative research, which have descriptive character’s and used lierature sosciology approach. The data analysis was used interactive model by Miles and Huberman, it was done by some ways, they were mark, clarification, and conclude the result analysis of hegenomy description in the social daily of Trilogi novel by Ahmad Tohari. The result of the research showed that there were seven description in the Trilogi Novel by Ahmad Tohari, it were include (1) Religion Hegenomy, it described conviction nitizen of Dukuh Paruk centered on Ki Secamenggala who was a representation of animism reliance, (2) Culture Tradition Hegenomy, it described the thinking and behavior of Dukuh paruk nitizen which bounded by the habits of his ancestors which considered kind and right, (3) Charismatic/authority hegenomy, it described about srintil as a paid dancing who has bewitch was able to controlled and influenced other people, (4) capitalist hegenomy, it described a priayi who reputed have authorization to the Dukuh Paruk Nitizen’s, (5) Materialism Hegenomy, it reflected the life’s of Dukuh Pruk nitizen who always consider as important material, (6) Militarism Hegenomy, it described the power of military as a hand of king goverment in handled a society, (7) politics hegenomy, it described a daily of Dukuh Paruk nitizen’s under authorization politics of the country in year 1965 which took in the adversity and destruction by the physycally or emotionally.